2009
DOI: 10.1130/ges00198.1
|View full text |Cite
|
Sign up to set email alerts
|

Fault interaction and along-strike variation in throw in the Pajarito fault system, Rio Grande rift, New Mexico

Abstract: The seismically active Pajarito fault system (PFS) of northern New Mexico, UnitedStates, is a complex zone of deformation made up of many laterally discontinuous faults and associated folds and fractures that interact in ways that have important implications for seismic hazards. Mapping and drilling projects in the PFS provide new insights into the structural geometry and paleoseismic history of the fault system. A 1.25 Ma old datum (the Bandelier Tuff) and high-resolution digital elevation data allow construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…The Pajarito fault system includes faults and monoclines of the Pajarito (PF), Rendija Canyon (RCF), Guaje Mountain (GMF) and Sawyer Canyon (SCF) faults. Map modified from Lewis et al (2009) pointed to three gradational stages of fumarolic activity as cooling proceeded: (1) high-temperature vapor phase degassing, (2) fumarolic gases interacting with water to create acids at the surface resulting in concentrated argillic alteration, and (3) present-day residual near-neutral steam emanations. Papike et al (1991) studied several fumarolic pipes at the Valley of Ten Thousand Smokes to determine chemical gains and losses, and mineralogic evolution.…”
Section: Introduction and General Settingmentioning
confidence: 99%
“…The Pajarito fault system includes faults and monoclines of the Pajarito (PF), Rendija Canyon (RCF), Guaje Mountain (GMF) and Sawyer Canyon (SCF) faults. Map modified from Lewis et al (2009) pointed to three gradational stages of fumarolic activity as cooling proceeded: (1) high-temperature vapor phase degassing, (2) fumarolic gases interacting with water to create acids at the surface resulting in concentrated argillic alteration, and (3) present-day residual near-neutral steam emanations. Papike et al (1991) studied several fumarolic pipes at the Valley of Ten Thousand Smokes to determine chemical gains and losses, and mineralogic evolution.…”
Section: Introduction and General Settingmentioning
confidence: 99%
“…Previous studies indicate that fault propagation and linkage may be an important process governing rift development. For example, in the Española Basin in northern New Mexico, multiple studies have been undertaken to decipher fault displacement profiles along the Pajarito fault system (Carter and Winter, 1995;Lewis et al, 2009;Goteti et al, 2013). Carter and Winter (1995) suggested that individual fault segments are generally bell shaped in the direction of dip, although they are asymmetric and displacement abruptly decreases at fault tips.…”
Section: Introductionmentioning
confidence: 99%
“…Carter and Winter (1995) suggested that individual fault segments are generally bell shaped in the direction of dip, although they are asymmetric and displacement abruptly decreases at fault tips. Lewis et al (2009) built upon these previous results and used the 1.25 Ma (Phillips, 2004) Tshirege Member of the Bandelier Tuff as a datum to construct a fault throw profile for the Pajarito fault system. Their results indicate that the Pajarito fault system is composed of multiple shorter segments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations